Pengelolaan Makanan Khas Ranau (Kue Gelang) Melalui Ibu PKK Dalam Pengenalan Budaya Di Kecamatan Buay Pematang Ribu Ranau Tengah - Putri , Selin Monica; Murdiati , Eni; Isnaini , Mohd Aji (CV. ITTC INDONESIA, 2023)
Bracelet cakes are one of the long-lasting snacks if stored properly, namely in a jar or other airtight container, as a treat for guests or a family snack. Bracelet cakes shaped like donuts with a sweet aroma from brown sugar are the creativity of making pastries. The creativity highlighted in this bracelet cake is in terms of its unique shape, which resembles a bracelet and tastes so sweet. The purpose of making this thesis entitled